Biological Degradation of Wood: Mechanisms of Decay and Modern Protection Strategies – A Review - Hasan, Omaima A (American Journal of Biology and Natural Sciences, 2026)
Wood is an efficient renewable material that has been extensively used in constructions, infrastructure and engineering products. However, in all of these applications the life of the service is significantly reduced due to biological degradation. Fungi, bacteria and insects are the main agents of the disintegration of wood, which thrive in favourable environmental conditions and take advantage of the lignocellulosic structure of the material. The current review provides an overview of the biological events that govern the degradation of wood, especially the fungal degradation, along with enzymatic and oxidative reactions. Moreover, it describes the effect of structural and chemical properties of wood on its resistance to decay, and thus provides a conceptual base on the appearance of biodeterioration. The review provides a critical assessment of traditional and innovative wood protection approaches, which include existing preservative regimes, moisture -management approaches, wood-modification approaches and nano - enabled bio-based interventions. Recent developments have brought about a paradigm shift in terms of integrated, biological responding protection concepts, where the material modification is co-ordinated with directed biological resistance. Although much has improved, the long-term sustainability, environmental compatibility, and cost-effectiveness are still problematic. The conclusion outlines the research directions that are important to perfect predictative service-life models and trigger the creation of the sustainable solution to the problem of the wood protection in the future.